2015
DOI: 10.1586/14787210.2015.1028366
|View full text |Cite
|
Sign up to set email alerts
|

Impact of special patient populations on the pharmacokinetics of echinocandins

Abstract: Echinocandins belong to the class of antifungal agents. Currently, three echinocandin drugs are licensed for intravenous treatment of invasive fungal infections: anidulafungin, caspofungin and micafungin. While their antifungal activity overlaps, there are substantial differences in pharmacokinetics (PK). Numerous factors may account for variability in PK of echinocandins including age (pediatrics vs adults), body surface area and body composition (normal weight vs obesity), disease status (e.g., critically il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 113 publications
5
30
0
Order By: Relevance
“…Recent studies revealed that the pharmacokinetics of echinocandins in special patient populations might impact clinical efficacy and safety (6). Septic cardiomyopathy is a wellknown organ dysfunction in sepsis, which is associated with reduced left ventricular contractility (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed that the pharmacokinetics of echinocandins in special patient populations might impact clinical efficacy and safety (6). Septic cardiomyopathy is a wellknown organ dysfunction in sepsis, which is associated with reduced left ventricular contractility (19).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, evidence is mounting that the pharmacokinetics of echinocandins in special patient populations prone to systemic inflammatory responses (e.g., critical ill patients, burn patients, patients with severe organ dysfunction) may impact clinical efficacy and safety (6).…”
mentioning
confidence: 99%
“…23 Though caspofungin, micafungin, and anidulafungin possess similar antifungal activities, the differences in their backbone structures lead to distinct pharmacokinetics. 88 Caspofungin may affect the plasma concentration of cyclosporine A and tacrolimus. 88 However, Saner et al demonstrated that co-administration of caspofungin with either of these 2 immunosuppressants in liver transplant patients resulted in an acceptable safety profile with no hepatotoxicity.…”
Section: Echinocandinsmentioning
confidence: 99%
“…88 Caspofungin may affect the plasma concentration of cyclosporine A and tacrolimus. 88 However, Saner et al demonstrated that co-administration of caspofungin with either of these 2 immunosuppressants in liver transplant patients resulted in an acceptable safety profile with no hepatotoxicity. 89 In addition, based on an open-label clinical trial in healthy adults, micafungin may increase exposure to amphotericin B about 30%; thus, it may not well tolerated during co-treatment in human host.…”
Section: Echinocandinsmentioning
confidence: 99%
“…significantly impact exposure of immunosuppressants [38,39]. Of note, one should be aware of a pharmacodynamic interaction between amphotericin B and calcineurin inhibitors as both classes of drugs have nephrotoxic properties [40].…”
Section: A No Known Interactionmentioning
confidence: 99%